ANALYSIS OF CROSS-ADAPTATION TO COLD EXPOSURE AND PHYSICAL EXERTION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The adaptive changes that occur in the body under the influence of hardening (dousing with a cold shower 2 times a day for 6 weeks) and running training on a treadmill (30 minutes at 70-80% of the individual maximum oxygen consumption, 3 times a week, for 6 weeks) were compared in 6 of the same subjects. The interval between the two sets of training was more than 3 months. The indicators recorded during the ramp test and the standard cold test before and after each training cycle were compared. It is shown that the patterns of adaptive shifts in adaptation to factors of different modalities are very different. Shifts in adaptation to physical activity turned out to be generally more pronounced than in adaptation to regular cold exposures. The individual diversity of adaptive reactions testifies to the expediency of developing new approaches in the theory of adaptation related to the study of physiological individuality.